Evolution in Management of Enterocutaneous Fistulas: An Historic Perspective and Updates - Berrones, Arianna Ruiz; Castrejón, Esperanza Sánchez; Ramírez, José Á. Tovar Ramírez; Ramos, R. Lucano Valdés Ramos; Ponce, Mariano Tovar Ponce; Biu, Alejandro Domínguez Biu; Hurtado, Mauricio Martínez; Talledos, Julio C. Matadamas; Jiménez, Saúl Martínez; Silva, Ludwigvan A. Bustamante (International Journal of Innovative Research in Medical Science, 2022)
Enterocutaneous fistulae (ECF) are a pathological entity that has increased in frequency since the advent of the open abdomen and damage control surgery, since in up to 85% of cases its origin is iatrogenic. The principles in the management of this nosological entity have been stipulated for more than 50 years [1], however evidence-based medicine and advances in some areas such as nutritional support and negative pressure systems have allowed us refine its management algorithm, discarding some ideas that were held as dogmas and establish less invasive therapies with better results for the patient.